Syndecan-1 as a Biomarker for Cardiovascular Risk in Patients with Behçet’s Disease - Kadıyoran, Cengiz; Yılmaz, Pınar Diydem; Göktepe, Mevlüt Hakan; Küçük, Adem; Oğul, Mustafa; Cüre, Erkan; Özdengül, Faik (Archives of Rheumatology, 2025)
Background/Aims: This study aimed to assess the potential of syndecan-1 levels as a biomarker for diagnosing cardiovascular diseases and atherosclerosis in patients with Behçet’s disease. Materials and Methods: After estimating the required sample size, 56 patients with Behçet’s disease and 56 age- and sex-matched controls were enrolled in the study. Carotid intima-media thickness (cIMT) was measured by a single radiologist using an appropriate technique. Syndecan-1 levels were determined with an Syndecan-1 human ELISA kit (CLOUD CLONE, USCN). The test system showed a correlation coefficient of 0.99 between expected and actual values, with a detection limit of around 0.01 ng/mL. The intra-assay coefficient of variation (CV) was under 10%, and the inter-assay CV was under 12%. Results: The data obtained from the study showed that syndecan-1 levels (P < .002) and cIMT measurements (P < .015) were significantly higher in patients with Behçet’s disease compared to the healthy control group. Additionally, correlation analysis revealed a significant negative relationship between syndecan-1 levels and cIMT. In a stepwise multiple regression analysis, a strong independent relationship was found between cIMT and age (beta [β] = 0.474, P < .001), syndecan-1 (β = 0.302, P = .007), and low-density lipoprotein (β = 0.219, P = .050). Conclusion: Syndecan-1 levels were higher in patients with Behçet’s disease compared to controls, and increased syndecan-1 may slow the progression of subclinical atherosclerosis. This study is a preliminary investigation. Further detailed studies are needed. Cite this article as: Kadıyoran C, Diydem Yılmaz P, Hakan Göktepe M, et al. Syndecan-1 as a biomarker for cardiovascular risk in patients with Behçet’s disease. Arch Rheumatol. 2025;40(4):435-442.